ANALISIS PERBEDAAN KEBIJAKAN KONTRATERORISME AMERIKA SERIKAT TERHADAP KELOMPOK TERORIS ISIL (Islamic State of Iraq and Levant) DAN BOKO HARAM TAHUN 2014 – 2016 - Sekarini Santoso, Nabilla Ayu; Rosyidin, Mohamad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
After 9/11, the U.S. have been so adamant on eradicating terrorism all over the world, and adopted a foreign policy that focuses on counterterrorism named „war on terror‟. The war on terror have been targeting terrorist groups like al-Qaeda, and most recently, its foremost focus is on ISIL. While the U.S. promised to erase all terrorism in the world, the policy still has some imbalance towards whom it applies to. Towards ISIL, the U.S. and its coalition have made subsequent progress on their counterterrorism efforts while towards other groups, such as Boko Haram, the policy application has been stagnant with not much progress. This thesis is a qualitative research using Mill‟s Method of comparative study to see the differences of each policy and will explore and analyze the reasons why the counterterrorism effort of the U.S. is unequal, focusing on its differences of counterterrorism policy towards ISIL and Boko Haram using Analytical Eclecticism as a tool. Furthermore, this thesis will also incorporate defensive realism and liberal internationalism to analyze the possible reasons on why U.S.‟s counterterrorism policy has a difference between whom it applies to. The result of this study shows that U.S. have a political interest in Syria including its rivalry with Russia and its needs to contain Russia‟s power in the Middle East and its interest to topple Assad from the Syrian government.